Family evaluation of an elderly with endemic goiter in primary health care (Research, Society and Development, 2020)
The family is the focus of attention of the Family Health Strategy (FHS). In this sense, using tools to approach the family can help the professional to get to know it, being able to analyze it in its context and more deeply the dynamics of family relationships and understand how it influences the health-disease-care process. For this purpose, a case study was carried out, with the objective of evaluating the functionality of a family in the district of jaibaras Sobral-CE, using the  APGAR tools for  family, genogram and ecomap. The index case was female, 60 years old, retired, married, diagnosed with systemic arterial hypertension and endemic goiter. The analysis showed a strong link between most family members and the index case, and a conflicting relationship between this and a son, who has bipolar disorder. In addition, the external structure showed us good monitoring of the FHS in relation to the health of all family members. Based on the application of the APGAR Familiar questionnaire, the family can be classified as having good functionality, since it obtained a score of eight. Thus, the findings point to the importance of developing strategies that involve health professionals in the use of assessment tools with families, encouraging them to adopt proximity to the context of the home and their social and health network throughout life, allowing effective and humanizing actions.